2023
DOI: 10.60084/hjas.v1i2.89
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Total Tannin Contents and Antimicrobial Activities in Methanol Extracts of Rhizophoraceae Species

Indriaty Indriaty,
Binawati Ginting,
Kartini Hasballah
et al.

Abstract: Rhizophoraceae is a large true mangrove family that produces mangrove tannins. Tannins have the potential to be used as antimutagenic, anticancer, antimicrobial, and antioxidant agents in the pharmaceutical and medical fields. The aim of the research was to determine the total tannin content, antimicrobial activity, and the correlation between the two in methanol extracts of four plant parts (roots, bark, leaves, and fruit/hypocotyl) from five Rhizophoraceae species, namely Bruguiera cylindrica, Bruguiera gymn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…As suggested by a previous study, qualitative screening is useful in the exploration of bioactive extracts. [ 5 20 ] For example, tannins might act as antioxidants (both primary and secondary) and antimicrobial agents. [ 5 20 21 ] Further, we found that the ethyl acetate extract had total phenolic content (TPC) as well as total flavonoid content (TFC) of 241.3 mg GAE/g dry extract and 51.08 mg QE/g dry extract, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As suggested by a previous study, qualitative screening is useful in the exploration of bioactive extracts. [ 5 20 ] For example, tannins might act as antioxidants (both primary and secondary) and antimicrobial agents. [ 5 20 21 ] Further, we found that the ethyl acetate extract had total phenolic content (TPC) as well as total flavonoid content (TFC) of 241.3 mg GAE/g dry extract and 51.08 mg QE/g dry extract, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[ 5 20 ] For example, tannins might act as antioxidants (both primary and secondary) and antimicrobial agents. [ 5 20 21 ] Further, we found that the ethyl acetate extract had total phenolic content (TPC) as well as total flavonoid content (TFC) of 241.3 mg GAE/g dry extract and 51.08 mg QE/g dry extract, respectively. As comparisons, the values indicating the TPC and TFC of the leaf extract of A. muricata in this present study are relatively higher, or at least similar, with those reported previously such as ethyl acetate extracts from Phyllanthus emblica stem barks, Limonia acidissima fruits, as well as Annona squamosa stem barks.…”
Section: Resultsmentioning
confidence: 99%
“…Indonesia is globally recognized for its vast tropical forests and biodiversity [1][2][3], including tobacco (Nicotiana tabacum L.) [4]. In 2019, Indonesia had a total national tobacco production of 197.40 thousand tons, making it one of the most widely cultivated crops in the country.…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia is a country rich in various types of plants, both from low to high levels [1,2]. Plant diversity has so many benefits for human life, one of which is as a traditional medicine [3,4]. Plants that are used as medicines get great attention in addition to providing beneficial physiological and pharmacological effects as well as to avoid the use of synthetic drugs that tend to have more side effects.…”
Section: Introductionmentioning
confidence: 99%